2022
DOI: 10.3389/fgene.2022.968228
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of integrin alpha 6 in human mesenchymal stem cells

Abstract: Human mesenchymal stem cells (MSCs) are isolated from various adult and perinatal tissues. Although mesenchymal stem cells from multiple sources exhibit similar morphology and cell surface markers, they differ in their properties. In this study, we determined that the expression of integrin alpha 6 (ITGA6) and ITGA6 antisense RNA (ITGA6-AS1) correlates with the proliferation, cell size, and differentiation potential. The expression of ITGA6 was inversely correlated with ITGA6-AS1 in MSCs. The expression of ITG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The integrin family is an important group of proteins, including integrin alpha (ITGA) and beta proteins. In ITGA, ITGA6, also known as CD49f, is a transmembrane glycoprotein adhesion receptor protein 22 . ITGA6-AS1, as an antisense non-coding RNA of ITGA6, can specifically target ITGA6 and lead to its increased expression, thereby regulating the occurrence and aggressiveness of breast cancer and secondary plasmacytic leukaemia 23 ( Figure 7 B ).…”
Section: Resultsmentioning
confidence: 99%
“…The integrin family is an important group of proteins, including integrin alpha (ITGA) and beta proteins. In ITGA, ITGA6, also known as CD49f, is a transmembrane glycoprotein adhesion receptor protein 22 . ITGA6-AS1, as an antisense non-coding RNA of ITGA6, can specifically target ITGA6 and lead to its increased expression, thereby regulating the occurrence and aggressiveness of breast cancer and secondary plasmacytic leukaemia 23 ( Figure 7 B ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression intensity of HSPB1, another heat-shock protein, has been correlated with the differentiation status of stem cells; HSPB1 is overexpressed in undifferentiating stem cells and downregulated in stem cells already committed towards a differentiation pathway [ 100 , 101 , 102 ]. ITGA6, an integrin α-6 or otherwise known as CD49f, has been shown to be expressed in various stem cells, having a significant role in self-renewal and proliferation [ 103 , 104 , 105 ]. MAPK1, otherwise known as Erk2, along with Erk1, are two kinases with significant roles in cell proliferation [ 106 , 107 , 108 ], and their expression has been shown to be crucial for the survival and self-renewal of hematopoietic stem cells [ 109 , 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CD90 level is decreased upon differentiation of MSCs (33,34). In contrast, CD49f is a self-renewal marker expressed in over 30 types of stem cells (35,36).…”
Section: Discussionmentioning
confidence: 99%